ANALYSIS OF SERVICE QUALITY ASSESSING CUSTOMER SATISFACTION WITH THE MAXIM APPLICATION THROUGH SERVICE QUALITY - Mukhlis, Mukhlis; Romadloni, Nova Tri (Yayasan Nuraini Ibrahim Mandiri, 2024)
Technological advancement has impacted every facet of human existence, including transportation. The internet plays a major role in people's daily lives these days. This study aims to investigate the effects of service quality principles on user satisfaction through empirical testing. Utilizing SPSS 23, data from surveys given to Maxim users will serve as a data source for testing the hypothesis. The partial analysis results back up the problem formulation by showing that the variables Emphaty (X4), Reliable (X1), Responsiveness (X2), Assurances (X3), and Tangible (X5) all have a small but positive effect on how satisfied Maxim application users are. Conversely, the concurrent study reveals a 51% positive impact on Maxim app users' enjoyment from the factors Resilience (X1), Responsiveness (X2), Assurances (X3), Emphaty (X4), and Tangibles (X5). Keywords: Maxim, Service quality, SPSS